# How To Prove It, Ch-3 Sec-3.7, More Examples of Proofs

## Chapter - 3, Proofs

### Summary

It contains few more examples to outline proofs which may contain multiple strategies.

Soln1

Existence:

Suppose $A = \cup \mathcal F$.

Proof for: $\mathcal F \subseteq \mathcal P(A)$:

Suppose $X \in \mathcal F$. Suppose $x \in X$, then $x \in \cup \mathcal F$. Since $x$ is arbitrary, we can say $X \subseteq \cup \mathcal F$. Since $X \subseteq \cup \mathcal F$, it follows that $X \in \mathcal P(\cup \mathcal F)$. Thus we have, if $X \in \mathcal F$, then $X \in \mathcal P(\cup \mathcal F)$. Since $X$ is arbitrary, it follows that $\mathcal F \subseteq \mathcal P(\cup \mathcal F)$.

Proof for: $\forall B(\mathcal F \subseteq \mathcal P(B) \to A ⊆ B)$:

Suppose $B$ is arbitrary. Suppose $\mathcal F \subseteq \mathcal P(B)$. Suppose $x \in A$, or $x \in \cup \mathcal F$. Then there must exist some set, say $X \in \mathcal F$ such that $x \in \mathcal F$. Since $\mathcal F \subseteq \mathcal P(B)$, it follows that $X \subseteq B$. Thus $x \in B$. Thus we have $x \in A \to x \in B$. Since $x$ is arbitrary, we can conclude $A \subseteq B$.

Uniqueness:

Suppose $A'$ is a set such that $\mathcal F \subseteq \mathcal P(A')$ and $\forall B(\mathcal F \subseteq \mathcal P(B) \to A' ⊆ B)$ are true. Now since this is true for all possible values of $B$ and we know that if $B = \cup \mathcal F$ then $\mathcal F \subseteq \mathcal P(B)$ is true. Thus if $B = \cup \mathcal F$, it follows that $A' \subseteq B$, or $A' \subseteq \cup \mathcal F$. Now suppose $x \in \cup \mathcal F$. Then there exists some set, say $X \in \mathcal F$ such that $x \in X$. But since $\mathcal F \subseteq \mathcal P(A')$, it follows that $X \in P(A')$, or $X \subseteq A'$. Thus $x \in A'$. Since $x$ is arbitrary, it follows that $\cup \mathcal F \subseteq A'$. Thus we have $A' \subseteq \cup \mathcal F \land \cup \mathcal F \subseteq A'$. It follows that $A' = \cup \mathcal F$.

Soln2

Existence:

Suppose $X \in \mathcal P(A \setminus B) \setminus (\mathcal P(A) \setminus \mathcal P(B))$. Thus we have:
$\leftrightarrow X \in P(A \setminus B) \land \lnot (X \in \mathcal P(A) \land X \notin \mathcal P(B))$
$\leftrightarrow X \in P(A \setminus B) \land (X \notin \mathcal P(A) \lor X \in \mathcal P(B))$

We know that every power set contains a set with empty element, or $\{ \phi \}$. Thus one possible value of $X = \{ \phi \}$ and it clearly satisfies the above statement.

Uniqueness:

Suppose if $X \ne \{ \phi \}$, then,
$\leftrightarrow X \in P(A \setminus B) \land (X \notin \mathcal P(A) \lor X \in \mathcal P(B))$
is equivalent to:
$\leftrightarrow X \subseteq (A \setminus B) \land (X \nsubseteq A \lor X \subseteq B)$
$\leftrightarrow (X \subseteq A \land X \nsubseteq B) \land (X \nsubseteq A \lor X \subseteq B)$

This can be true only in following cases:

• $X \subseteq A \land X \nsubseteq B \land X \nsubseteq A$:
Clearly this is not possible.

• $X \subseteq A \land X \nsubseteq B \land X \subseteq B$: Clearly this is also not possible.

Thus it contradicts the assumption that such set $X \ne \{ \phi \}$ exists.

Thus there is only one such set $X = \{ \phi \}$.

Soln3

We shall prove this as follows :

1. if (a) then (b).
2. if (b) then (c).
3. if (c) then (a).

where (a), (b) and (c) are the parts given in the problem.

- if (a) then (b).

Suppose (a), is true. Thus $(A \triangle C) \cap (B \triangle C) = \phi$ is true.

We will prove this part : $A \cap B \subseteq C$ by contradiction. Suppose $x \in A \cap B$. Suppose $x \notin C$. Since $x \in A \land x \notin C$, it follows that $x \in A \triangle C$. Similarly, since $x \in B \land x \notin C$, it follows $x \in B \triangle C$. Thus $A \triangle C) \cap (B \triangle C) \ne \phi$. But this contradicts with the assumption $(A \triangle C) \cap (B \triangle C) = \phi$. Thus we have if $x \in A \cap B$, then $x \in C$. Since $x$ is arbitrary, we can conclude $A \cap B \subseteq C$.

Now we will prove part : $C \subseteq A \cup B$ by contradiction. Suppose $x \in C$. Suppose $x \notin (A \cup B)$. It follows that $\lnot (x \in A \lor x \in B$, which is equivalent to $x \notin A \land x \notin B$. Since $x \in C \land x \notin A$, it follows that $x \in A \triangle C$. Similarly, since $x \in C \land x \notin B$, it follows that $x \in B \triangle C$. Thus $(A \triangle C) \cap (B \triangle C) \ne \phi$, which contradicts our assumption. Thus if $x \in C$, then $x \in (A \cup B)$. Since $x$ is arbitrary, we can say that $C \subseteq A \cup B$.

- if (b) then (c).

Suppose (b) is true. Thus $A \cap B \subseteq C \subseteq A \cup B$ is true. Suppose $x \in A \triangle C$, then we have following possible cases:

• Case 1: $x \in A$, $x \notin C$, $x \in B$: This case is not possible because we know that if $x \in A \cap B$, then $x \in C$.

• Case 2: $x \in A$, $x \notin C$, $x \notin B$: Thus $x \in A \setminus B$. It follows that $x \in A \triangle B$.

• Case 3: $x \in C$, $x \notin A$, $x \in B$: Thus $x \in B \setminus A$. It follows that $x \in A \triangle B$.

• Case 4: $x \in C$, $x \notin A$, $x \notin B$: This case is not possible because we know that if $x \in C$, then $x \in A \cup B$.

Thus from all the cases, if $x \in A \triangle C$, then $x \in A \triangle B$. Since $x$ is arbitrary, we can conclude that $A \triangle C \subseteq A \triangle B$.

- if (c) then (a).

Suppose (c) is true. Thus $A \triangle C \subseteq B \triangle C$ is true. Suppose $x \in A \triangle C$. It follows that $x \in A \triangle B$. Thus we have following cases:

• Case 1: $x \in A \setminus C$, $x \in A \setminus B$: In this case $x \notin B \setminus C$. It follows that $x \notin B \triangle C$.

• Case 2: $x \in A \setminus C$, $x \in B \setminus A$: This case is not possible as $x \in A \land x \notin A$ is not possible.

• Case 3: $x \in C \setminus A$, $x \in A \setminus B$: This case is also not possible as $x \notin A \land x \in A$ is not possible.

• Case 4: $x \in C \setminus A$, $x \in B \setminus A$: Since $x \in B \land x \in C$, it follows that $x \notin B \triangle C$.

Thus from all the cases we have, $x \notin B \triangle C$. Since $x$ is arbitrary, we can conclude that $(A \triangle C) \cap (B \triangle C) = \phi$.

Soln4

Suppose $\mathcal P(\cup_{i \in I} A_i) \subseteq \cup_{i \in I} \mathcal P(A_i)$. Thus if $X \in \mathcal P(\cup_{i \in I} A_i)$, then $X \in \cup_{i \in I} \mathcal P(A_i)$. Since $\cup_{i \in I} A_i \in P(\cup_{i \in I} A_i)$, it follows that $\cup_{i \in I} A_i \in \cup_{i \in I} \mathcal P(A_i)$. Thus $\cup_{i \in I} A_i$ exists in at-least one of the sets, say $\mathcal P(A_i)$ in $\cup_{i \in I} \mathcal P(A_i)$. Thus we have $\cup_{i \in I} A_i \subseteq A_i$. Now suppose $j \in I$, then $A_j \subseteq \cup_{i \in I} A_i$. And since $\cup_{i \in I} A_i \subseteq A_i$, we can conclude that $A_j \subseteq A_i$. Since $j$ is arbitrary, we can conclude that $\forall j \in I (A_j \subseteq A_i)$.

Soln5

(a)

Suppose $x \in \cup_{i \in I} A_i$. Thus we have:
$\leftrightarrow \exists i \in I ( x \in A_i )$
$\leftrightarrow \exists i(i \in I \land x \in A_i )$
Since $I = \cup \mathcal F$,
$\leftrightarrow \exists i(i \in \cup \mathcal F \land x \in A_i )$
$\leftrightarrow \exists i(\exists X \in \mathcal F(i \in X) \land x \in A_i )$
$\leftrightarrow \exists i(\exists X (X \in \mathcal F \land i \in X) \land x \in A_i )$
$\leftrightarrow \exists i(\exists X (X \in \mathcal F \land i \in X \land x \in A_i ))$
$\leftrightarrow \exists i \exists X (X \in \mathcal F \land i \in X \land x \in A_i )$
$\leftrightarrow \exists X \exists i (X \in \mathcal F \land (i \in X \land x \in A_i ))$
$\leftrightarrow \exists X (X \in \mathcal F \land \exists i (i \in X \land x \in A_i ))$
$\leftrightarrow \exists X (X \in \mathcal F \land x \in \cup_{i \in X}A_i)$
$\leftrightarrow \exists X \in \mathcal F(x \in \cup_{i \in X}A_i)$
$\leftrightarrow x \in \cup_{X \in \mathcal F} (\cup_{i \in X}A_i)$

Since $x$ is arbitrary, we can conclude $\cup_{i \in I} A_i = \cup_{X \in \mathcal F} (\cup_{i \in X}A_i)$.

(b)

Suppose $x \in \cap_{i \in I} A_i$. Thus we have:
$\leftrightarrow \forall i \in I ( x \in A_i )$
$\leftrightarrow \forall i(i \in I \to x \in A_i )$
Since $I = \cup \mathcal F$,
$\leftrightarrow \forall i(i \in \cup \mathcal F \to x \in A_i )$
$\leftrightarrow \forall i( \exists X \in \mathcal F(i \in X) \to x \in A_i )$
$\leftrightarrow \forall i( \exists X(X \in \mathcal F \land i \in X) \to x \in A_i )$
$\leftrightarrow \forall i( \lnot \exists X(X \in \mathcal F \land i \in X) \lor x \in A_i )$
$\leftrightarrow \forall i( \forall X \lnot (X \in \mathcal F \land i \in X) \lor x \in A_i )$
$\leftrightarrow \forall i( \forall X (X \notin \mathcal F \lor i \notin X) \lor x \in A_i )$
$\leftrightarrow \forall i( \forall X (X \notin \mathcal F \lor i \notin X \lor x \in A_i ))$
$\leftrightarrow \forall i \forall X (X \notin \mathcal F \lor i \notin X \lor x \in A_i )$
$\leftrightarrow \forall X \forall i (X \notin \mathcal F \lor (i \notin X \lor x \in A_i) )$
$\leftrightarrow \forall X (X \notin \mathcal F \lor \forall i(i \notin X \lor x \in A_i) )$
$\leftrightarrow \forall X (X \notin \mathcal F \lor \forall i(i \in X \to x \in A_i) )$
$\leftrightarrow \forall X (X \notin \mathcal F \lor x \in \cap_{i \in X}A_i )$
$\leftrightarrow \forall X (X \in \mathcal F \to x \in \cap_{i \in X}A_i )$
$\leftrightarrow x \in \cap_{X \in \mathcal F}(\cap_{i \in X}A_i ))$

Since $x$ is arbitrary, we can conclude $\cap_{i \in I} A_i = \cap_{X \in \mathcal F} (\cap_{i \in X}A_i)$.

(c)

Suppose $x \in \cup_{i \in J}A_i$. Thus $x$ exist in atleast one of the sets, say $A_k$, such that $k \in \cap \mathcal F$. Thus $k$ exist in all the sets of $\mathcal F$. Thus for any set, say $X \in \mathcal F$, we have $k \in X$. Thus if $x \in A_k$, then $x \in \cup_{i \in X}A_i$ because $k \in X$. Since $X$ can be any set such that $X \in F$, it follows that $x$ exists in all the sets $\cup_{i \in X}A_i$ such that $X \in \mathcal F$. Thus $x$ also exists in $\cap_{X \in \mathcal F} (\cup_{i \in X}A_i)$. Since $x$ is arbitrary, we can conclude that $\cup_{i \in J}A_i \subseteq \cap_{X \in \mathcal F} (\cup_{i \in X}A_i)$.

Counterexample for: $\cap_{X \in \mathcal F} (\cup_{i \in X}A_i) \subseteq \cup_{i \in J}A_i$:

Suppose $\mathcal F = \{ \{1, 2\}, \{1, 3\} \}$
$I = \cup \mathcal F = \{1, 2, 3\}$
$J = \cap \mathcal F = \{1\}$

Suppose $A_1 = \{a, b, c\}$, $A_2 = \{b, c, d\}$, $A_3 = \{d, e, f\}$.

Thus $\cup_{i \in J}A_i = A_1 = \{a, b, c\}$
And $\cap_{X \in \mathcal F} (\cup_{i \in X}A_i) = (A_1 \cup A_2) \cap (A_1 \cup A_3) = \{a, b, c, d\} \cap \{a, b, c, d, e, f\} = \{a, b, c, d\}$.

Thus $\cap_{X \in \mathcal F} (\cup_{i \in X}A_i) \nsubseteq \cup_{i \in J}A_i$.

(d)

We shall prove the theorem $\cup_{X \in \mathcal F}(\cap_{i \in X} A_i ) \subseteq \cap_{i \in J} A_i$.

Suppose $x \in \cup_{X \in \mathcal F}(\cap_{i \in X} A_i)$. Thus $x$ must exist in atleast one of the set, $\cap_{i \in P} A_i$, such that $P \in \mathcal F$. Since $x \in \cap_{i \in P} A_i$, and $J \subseteq P$, it follows that $x$ must exist in $\cap_{i \in J} A_i$. Thus we can conclude that if $x \in \cup_{X \in \mathcal F}(\cap_{i \in X} A_i )$, then $x \in \cap_{i \in J} A_i$.

Suppose $\mathcal F = \{ \{1, 2\}, \{1, 3\} \}$
$I = \cup \mathcal F = \{1, 2, 3\}$
$J = \cap \mathcal F = \{1\}$

Suppose $A_1 = \{a, b, c\}$, $A_2 = \{b, c, d\}$, $A_3 = \{b, d, e\}$.

Thus $\cap_{i \in J}A_i = A_1 = \{a, b, c\}$
And $\cup_{X \in \mathcal F} (\cap_{i \in X}A_i) = (A_1 \cap A_2) \cup (A_1 \cap A_3) = \{b, c\} \cup \{b\} = \{b, c\}$.

Thus $\cap_{i \in J} A_i \nsubseteq \cup_{X \in \mathcal F}(\cap_{i \in X} A_i )$.

Soln6

Suppose $\varepsilon > 0$ is arbitrary. Suppose $\delta = \frac {\varepsilon} 3$. Suppose $x$ is an arbitrary real number and $0 < \vert x - 2 \vert < \delta$. Then we have: $\vert \, \frac {3x^2 - 12} {x-2} - 12 \, \vert$, is equivalent to:
$\leftrightarrow \vert \, \frac {3x^2 - 12x + 12} {x-2} \, \vert$
$\leftrightarrow \vert \, \frac {3(x^2 - 4x + 4)} {x-2} \, \vert$
$\leftrightarrow \vert \, \frac {3(x - 2)^2} {x-2} \, \vert$
Since $0 < \vert\,x - 2\,\vert < \delta$, thus $x - 2 \ne 0$
$\leftrightarrow \vert \, 3(x - 2) \, \vert$
Since $0 < \vert\,x - 2\,\vert < \delta$:
$\vert \, 3(x - 2) \, \vert < 3 \delta$
$\leftrightarrow \vert \, 3(x - 2) \, \vert < 3 \times \frac {\varepsilon} 3$
$\leftrightarrow \vert \,3(x - 2) \, \vert < \varepsilon$

Thus, $\vert \, \frac {3x^2 - 12x + 12} {x-2} \, \vert < \varepsilon$

Soln7

Suppose that $\lim_{x \to c} f(x) = L$. Thus for all $\varepsilon > 0$, there exists a $\delta$ such that for all $x$, if $0 < \vert\,x - c\,\vert < \delta$, then

$\vert f(x) - L \vert < \varepsilon$.
Since $L > 0$, if $\varepsilon = L$, then:
$\vert f(x) - L \vert < L$.
$= -L < f(x) - L < L$.
$= 0 < f(x) < 2L$.

Thus $f(x) > 0$.

Soln8

Suppose that $\lim_{x \to c} f(x) = L$. Thus for all $\varepsilon > 0$, there exists a $\delta$ such that for all $x$, if $0 < \vert\,x - c\,\vert < \delta$, then

$\vert f(x) - L \vert < \varepsilon$.
$\leftrightarrow 7 \times \vert f(x) - L \vert < 7 \times \varepsilon$.
$\leftrightarrow \vert 7f(x) - 7L \vert < 7 \varepsilon$.

Since $\varepsilon > 0$, $7 \varepsilon > 0$.

Thus, if $0 < \vert\,x - c\,\vert < \delta$, then $\leftrightarrow \vert 7f(x) - 7L \vert < \varepsilon'$, where $\varepsilon' = 7 \varepsilon > 0$.

Thus $\lim_{x \to c} 7 f(x) = 7L$.

Soln9

The proof and theorem both are correct. Following strategies are used:

1. To prove a goal of the form of $\exists x P(x)$. Here existential instantiation is used.
2. To prove a goal of the form of $P \lor Q$, all possible cases are considered.